What if an asteroid hit earth? - Cefrey, Holly (New York : Children's Press, 2002)
Discusses what might happen if an asteroid hit the Earth.
Includes index.
G5
Keywords: Asteroids -- Collisions with Earth -- Environmental aspects -- Juvenile literature; Catastrophes (Geology) -- Juvenile literature; Asteroids; Disasters